Effect of Mulching, Sanitation and Yellow Fluorescent Sticky Trap Application on Population Fluctuation and Critical Attack Period of Thrip on Mangosteen - ., Affandi; Emilda, Deni (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2010)
This research aims to know the effect of mulching, sanitation and yellow fluorescent sticky trap application on population fluctuation and critical attack period of thrip on mangosteen which was carried out in a farmer mangosteen orchard in Lima Puluh Kota district, West Sumatra, Indonesia from October 2007 to February 2008. Twenty of plants were used as sampling units. Four plants were used to elucidate the critical period of mangosteen thrip attack that was assessed based on parameter of scar intensity, and sixteen plants were used to study the effects of mulching, sanitation and yellow fluorescent sticky trap on population fluctuation of mangosteen thrips. Each treatment was replicated four times. A completely randomized design was applied and continued with Lowest Significant Different to identity the differences among the treatments. The result showed that critical period of mangosteen thrip was at the 3rd - 10th weeks after fell of calyx. Sanitation combined with application of yellow fluorescent sticky trap reduced percentage and intensity of scars valueby 32.83 % and 5.99 %, respectively. The present study implies that knowledge of mangosteen thrip critical attack period and suitable controlling technique are important for the success of thrip control.Keywords : mangosteen, thrips, critical period, control